1998
DOI: 10.1159/000022433
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and Fibrinolysis Markers and Risk of Dementia

Abstract: We performed a cross-sectional case-control study among 277 subjects with dementia and 298 control subjects drawn from participants of the Rotterdam Study, a population-based cohort study among subjects aged 55 years or over, and from participants of the Rotterdam Stroke Databank, a hospital-based stroke registry, with the objective to evaluate the association of indicators of coagulability, fibrinogen, prothrombin fragments 1+2, thrombin-antithrombin complex (TAT), and indicators of fibrinolysis, plasmin-inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 15 publications
4
38
0
Order By: Relevance
“…DISCUSSION In the present study, we promote the hypothesis that the complex pathologies of AD and DLB are reflected in concentrations of plasma and CSF inflammatory markers. [38][39][40][41][42] To * Associations between the levels of measured variables and Alzheimer disease (AD) vs controls. † Associations between the levels of measured variables and dementia with Lewy bodies (DLB) vs controls.…”
Section: Results Patient Characteristicsmentioning
confidence: 99%
“…DISCUSSION In the present study, we promote the hypothesis that the complex pathologies of AD and DLB are reflected in concentrations of plasma and CSF inflammatory markers. [38][39][40][41][42] To * Associations between the levels of measured variables and Alzheimer disease (AD) vs controls. † Associations between the levels of measured variables and dementia with Lewy bodies (DLB) vs controls.…”
Section: Results Patient Characteristicsmentioning
confidence: 99%
“…In a nested case-control study from the Rotterdam cohort, D-dimer, thrombin-antithrombin complexes, and tissue plasminogen activator were all associated with increased risk of dementia. 6 We have previously published on community-dwelling subjects with atrial fibrillation, in whom elevated D-dimer is associated with development of dementia. 21 D-dimer is also associated with increased disability in older populations.…”
Section: Discussionmentioning
confidence: 99%
“…5 Dementia is associated with increased levels of thrombin-antithrombin complexes, D-dimer, and tissue plasminogen activator. 6 Hemostatic activation, including elevated D-dimer, may also be associated with increased risk of disability. 7 However, further research, including prospective longitudinal data, is required to clarify the strength of association of markers of hemostatic function with functional and cognitive decline in older age.…”
mentioning
confidence: 99%
“…Various cohort and case-control-based studies have described an apparent association between higher levels of blood markers of thrombosis and haemostasis and incident dementia or cognitive decline (Bots et al 1998;Gallacher et al 2010;Stott et al 2010). Recent systematic review and meta-analysis have confirmed this link with blood markers; observed associations were strongest for Bvascular^dementia but also apparent for Ballcause^(undifferentiated) dementias (Quinn et al 2011).…”
Section: Introductionmentioning
confidence: 98%